Geometric Harmonization Characteristics of Samarkand Registan Ensemble - Djumakulov Fazil Uzokovich; Dostonov Alisher Saydullaevich (International Journal on Orange Technologies, 2022)
This article analysis the secrets of geometric harmony and correlation of the Samarkand Registan ensemble. Also, in the article were proved the regularities of architectural harmonization of buildings in relation to the Registan Square and the issues of proportionality between the squares of the three madrasahs and the Registan Square.